Policies to promote import of technologies into developing countries: experiences from Asian countries - Long, Hoang Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Successes achieved from import of technologies of some developing countries in Asia are closely linked to efforts to build up and to implement related policies. The most impacts coming from these policies are supports for domestic enterprises to import technologies, to encourage external sides to transfer technologies, to administer the import of technologies and to enhance local capacities for import of technologies. In this context, certain flexible measures were applied for implementation of policies of import of technologies. Code: 16061001